2016
DOI: 10.1101/lm.042721.116
|View full text |Cite
|
Sign up to set email alerts
|

Deleting both PHLPP1 and CANP1 rescues impairments in long-term potentiation and learning in both single knockout mice

Abstract: Calpain-1 (CANP1) has been shown to play a critical role in synaptic plasticity and learning and memory, as its deletion in mice results in impairment in theta-burst stimulation-(TBS) induced LTP and various forms of learning and memory. Likewise, PHLPP1 (aka SCOP) has also been found to participate in learning and memory, as PHLPP1 overexpression impairs hippocampus-dependent learning. We previously showed that TBS-induced LTP was associated with calpain-1 mediated truncation of PHLPP1.To better understand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Calpains, which are localized in spines [ 69 , 70 ], have been suggested to mediate changes in the cytoskeletal structure and organization [ 42 , 71 ] by cleaving substrate proteins [ 60 , 61 ]. The genetic deletions of the calpain 1 / calpain 2 genes resulted in the decline in spine density and dendritic branching complexity in hippocampal CA1 pyramidal neurons, which further impaired the induction of LTP by theta burst stimulation in the CA1 area of the hippocampus [ 44 , 72 , 73 ]. Interestingly, recent studies have suggested distinct roles of calpain 1 and 2 in synaptic plasticity [ 45 ]; calpain 1 is required for the induction of LTP while calpain 2 is necessary for this maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Calpains, which are localized in spines [ 69 , 70 ], have been suggested to mediate changes in the cytoskeletal structure and organization [ 42 , 71 ] by cleaving substrate proteins [ 60 , 61 ]. The genetic deletions of the calpain 1 / calpain 2 genes resulted in the decline in spine density and dendritic branching complexity in hippocampal CA1 pyramidal neurons, which further impaired the induction of LTP by theta burst stimulation in the CA1 area of the hippocampus [ 44 , 72 , 73 ]. Interestingly, recent studies have suggested distinct roles of calpain 1 and 2 in synaptic plasticity [ 45 ]; calpain 1 is required for the induction of LTP while calpain 2 is necessary for this maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…These data point to a model in which SCOP regulates anxiety by modulating AKT/GSK3β signaling. In addition, SCOP has been shown to regulate K-Ras/ERK signaling in the hippocampus 24 40 . MAPK/ERK signaling in the amygdala has been repeatedly shown to contribute to anxiety regulation in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have provided clear evidence that calpain-1 plays a critical role in synaptic plasticity and learning and memory, as well as in the maturation of the CNS. Thus, calpain-1 KO mice are impaired in theta burst stimulation-(TBS) induced long-term potentiation (LTP) of synaptic transmission in hippocampus and in various forms of learning and memory (Liu et al, 2016;Heysieattalab et al, 2019). They also exhibit a mild form of cerebellar ataxia resulting from the immaturity of the synaptic contacts between the parallel fibers and the Purkinje neurons in cerebellum (Wang et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%